Effectiveness of Nano-hydroxyapatite in Caries Prevention: Literature Review - Sulistyawati, Tri; Cahyani, C (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Introduction: Enamel, as the most resilient biological tissue found in the human organism, comprises an estimated 96% inorganic matter. The principal constituent, which confers upon enamel its characteristic translucency and pristine white appearance, is Hydroxyapatite (HA). Ithe realm of dentistry, the emergence of nanohydroxyapatie (nHA) has garnered noteworthy recognotion owing to its exceptional hydroxyapatite. Dentistry has witnessed the assimilation of nHA into diverse dental formulations and materials, thereby fostering comprehensive oral healthcare practices. Notably, a prominent utilization of nHA lies in its role in the prevention of dental caries, leading to development of remineralization pastes. These products aim to enhance remineralization and protect the tooth surface. Additionally, nHA based materials have shown promise in restoring dental defects such as caries, fractures and tooth loss. Overall, nHA holds potential for advancing preventive and restorative dentistry. Objectives: The objective of this literature review is to assess the effectiveness of nano-hydroxyapatite in preventing dental caries. Methods: A thorough review of pertinent research, studies, and publications will beundertaken, specifically examining the role nHA in preventing dental caried. The chosen articles will undergo critical evaluation to assess the overall efficacy of nHA in caries prevention. Result: The deposition of mineral on carious lesions can be facilitated by the remarkable capacity of nanohydroxyapatite. Through its chemical affinity with apatite crystals, nanohydroxyapatite aids in the remineralization of enamel caries by generating a uniform apatite layer on the demineralized surface of the enamel. Conclusions: Based on this comprehensive analysis of existing literature, it can be inffered that nanohydroxyapatite (nHAP) exhibits the potential to stimulate mineralization on incipient carious lesions by effectively permeating the porous tooth structure resulting from the caries process. Consequently, this infiltration enhances the mineral content and hardness of the affected tooth structure.